PENGGUNAAN E-MODUL HIDROLISIS GARAM BERBASIS PROBLEM BASED LEARNING DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP HASIL BELAJAR KOGNITIF MURID KELAS XI SMAN 14 PADANG - Septiani Andilla Putri; Iryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The abstract nature of salt hydrolysis often triggers learning difficulties for students. Based on observations and interviews with chemistry teachers at SMAN 14 Padang, approximately 56% of students struggled to understand this concept, particularly in determining properties and calculating the pH of solutions, which resulted in the underachievement of the Learning Objective Achievement Criteria (KKTP). To address this issue, a Problem-Based Learning (PBL)-based salt hydrolysis e-module integrated with the Teaching at the Right Level (TaRL) approach was implemented to boost students' cognitive learning outcomes. This quasi-experimental study, employing a Nonequivalent Control Group Design, used a purposive sampling technique to assign class XI F1 as the experimental group (30 students) and class XI F2 as the control group (30 students). Data gathered through multiple-choice objective tests were analyzed, showing that all data were normally distributed and homogeneous. The experimental class achieved a significantly higher post-test mean score of 85.73 compared to the control class, which only reached 78.80. This result was reinforced by a t-test yielding a t count of 3.091, which is higher than the ttable of 2.002 at a significance level of 0.003. Furthermore, the effectiveness of the TaRL approach was evident from the N-Gain index of the Bromine (0.7342), Chlorine (0.8056), and Fluorine (0.8752) groups, all of which fell into the high category. Consequently, it can be concluded that the use of this PBL-TaRL-based e-module is highly effective in improving students' cognitive learning outcomes through an adaptive learning model.